Complementary feeding practices among children under two years old in west Africa: a review - Mitchodigni, I.M.; Amoussa Hounkpatin, Waliou; Ntandou-Bouzitou, Gervais D.; Termote, Céline; Bodjrènou, Fifali Sam Ulrich; Mutanen, M.; Hounhouigan, Djidjoho J. (African Journal of Food, Agriculture, Nutrition and Development, 2018)
The burden of child malnutrition is still high in West African countries with 19.2 million stunted children and increases rapidly during the weaning period. This has been attributed to inappropriate complementary feeding practices. To our knowledge, few studies have tried to review the state of complementary feeding in the sub-region. This review aimed to provide an overview of current complementary feeding practices in West Africa in order to identify issues that should be targeted for ensuring optimal infant and young child nutrition. Articles and reports published from 2006 to 2016 were selected and reviewed. All documents were accessed through PubMed, Google scholar, and FreeFullPDF databases. Relevant and current documents focused on infant and young child (IYC) feeding from World Health Organization (WHO) and the United Nations Children’s Fund (UNICEF) were identified by using electronic searches via the Google platform. Complementary feeding practices are suboptimal in West Africa compared to the Northern Africa. Porridges and family dishes are the two main categories of complementary foods given to children and there are nutritionally inadequate. Enriched flours have been developed by using local diversity of food resources and improved food process like dehulling, fermentation, germination, malting, but their use remains low. Socio-economic, cultural and geographical factors were the determinants influencing IYC feeding practices at mother and household levels. Besides food availability, social, cultural, economic and geographic determinants were interrelated in a complex way to affect child feeding practices. This paper contributes to a much-needed evidence-based focus on the state of complementary feeding practices. As a key component to child survival, the improvement of complementary feeding has been shown to be the most effective in enhancing child growth and reducing stunting. Stakeholders such as policy and decision-makers, development partners, the private sector, and Non-Governmental Organizations should develop strategies for making enriched flours and nutritionally dense foods more accessible and affordable. Nutritional interventions should emphasize the promotion of adequate complementary feeding practices including feeding frequency, quality and quantity of diet and food safety in order to reduce malnutrition. Ongoing national plans and strategies for optimal IYC feeding should be encouraged to reduce child malnutrition.